On the exponential Radon transform and its extension to certain functions spaces - Al-Omari, Shrideh Khalaf Qasem; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
We investigate the exponential Radon transform on a certain function space of generalized functions. We establish certain space of generalized functions for the cited transform. The transform that is obtained is well defined. More properties of consistency, convolution, analyticity, continuity, and sufficient theorems have been established.